Depression in cancer : the many biobehavioral pathways driving tumor progression - Bortolato, Beatrice (2017)
Major Depressive Disorder (MDD) is common among cancer patients, with prevalence rates up to four- times higher than the general population. Depression confers worse outcomes, including non- adherence to treatment and increased mortality in the oncology setting. Advances in the understanding of neurobiological underpinnings of depression have revealed shared biobehavioral mechanisms may contribute to cancer progression. Moreover, psychosocial stressors in cancer promote: (1) inflammation and oxidative/nitrosative stress; (2) a decreased immunosurveillance; and (3) a dysfunctional activation of the autonomic nervous system and of the hypothalamic–pituitaryadrenal axis. Consequently, the prompt recognition of depression among patients with cancer who may benefit of treatment strategies targeting depressive symptoms, cognitive dysfunction, fatigue and sleep disturbances, is a public health priority. Moreover, behavioral strategies aiming at reducing psychological distress and depressive symp- toms, including addressing unhealthy diet and life-style choices, as well as physical inactivity and sleep dysfunction, may represent important strategies not only to treat depression, but also to improve wider cancer-related outcomes. Herein, we provide a comprehensive review of the intertwined biobehavioral pathways linking depression to cancer progression. In addition, the clinical implications of these findings are critically reviewed.